Harga Yang Berkeadilan Dalam Perspektif Ekonomi Islam Dan Pengaruhnya Terhadap Keputusan Pembelian Ayam Geprek Di Pamekasan - Taufik Aris Saputra (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to analyze the influence of price on purchasing decisions of Ayam Geprek at Tok Patok Outlet located in Panaan Village, Palengaan District, Pamekasan Regency. Tok Patok is one of the culinary brands that has rapidly expanded in Madura, founded by Agus Pranajaya from Sidoarjo, with one of its branches managed by Mrs. Masrufah, who also serves as a caretaker of Mambaul Ulum Islamic Boarding School, Bata-Bata. This research applies a quantitative approach with a survey method involving consumers who made purchases at Tok Patok Panaan Outlet. The independent variable in this study is price, while the dependent variable is purchasing decision. The menu offered consists of four packages ranging from IDR 10,000 to IDR 14,000, with a complimentary bottle of mineral water for each package purchased. Data analysis using simple linear regression produced the equation Y = 0.070 + 0.701X + e, indicating that price has a positive and significant effect on purchasing decisions. This means that each increase in affordable and consumer-expected pricing will enhance purchasing decisions by 70.1%. These findings confirm that competitive pricing strategies play a dominant role in shaping consumer preferences and loyalty. The results are expected to serve as a reference for Tok Patok’s management in formulating effective marketing strategies. Keywords: Price; Purchasing Decision; Ayam Geprek; Tok Patok; Pamekasan